Pemphigus foliaceus: report of a case - Delgadillo Ávila, Juana (2009)
This is a case reporta case of Pemphigus Foliaceus in a 34 year-old male referred to the Arzobispo Loayza Hospital, which was evaluated and subjected to different examinations for diagnosis and treatment. Pemphigus Foliaceus is included in the blistering diseases, which is considered a chronic and relatively benign variety of pemphigus, where the patient's general condition is affected very little. It is considered as an autoimmune disease of unknown etiology that is characterized by deposition of auto-antibodies: Immunoglobulins and complement to the intercellular junctions. As any heafth professional, the dentist must have knowledge of the clinical and general mouth to help in the differential diagnosis of the disease.